PERTIMBANGAN, PENGETAHUAN, DAN SIKAP KONSUMEN INDIVIDU TERHADAP BANK SYARIAH - Adawiyah, Wiwiek Rabiatul (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This study aimed at finding out the selection criteria considered by individual customers in choosing Islamic (Syariah) banks; assessing the degree of customers knowledge on Islamic banks products; and finally to determine customersâ attitudes towards Islamic banks. The sample of the study was individual customers of Bank Muamalat and Bank Syariah Mandiri located in Banyumas Regency. There were two steps employed in analyzing the data: descriptive and factor analysis. The result of the study shows that there are seven factors to be considered by customers in patronizing Islamic banks. Among those factors are: perception, process, tangible, price, people, social and location. The most important factor considered by customers is perception factor. Moreover, customersâ knowledge on Islamic banks is still narrow, some do not even familiar with the products offered by Islamic banks. Religion is not the main reason for customer to patronize Islamic bank, other important reason is the level of profit sharing offered by the banks.